Tindak Tutur Representatif Dalam Pembimbingan Tugas Akhir pada Program Studi Pendidikan Geografi Universitas Sembilanbelas November Kolaka - Takwa, Takwa; Nasir, Agus; Widiyawati, Eka (GERAM: Gerakan Aktif Menulis, 2022)
This study aims to determine the types of representative speech acts used by students and lecturers of Geography education at the Nineteen November Kolaka University in carrying out their final assignment guidance. This type of research is qualitative using the content analysis method, which focuses on the types of speech of students and lecturers. Data collection techniques using observation, record and notes. The data analysis technique uses data reduction, data presentation and conclusion. The results of this study indicate that there are 8 types of representative speech acts used by students and lecturers of Geography education in conducting final assignment guidance, namely representative speech acts of retrodictive, descriptive, informative, confirmative, retractive, dissentive, disputative, suggestive, in this study were not found predictive and suppositive types.